A BORDERLAND DISCOURSE ANALYSIS ON ENGLISH LANGUAGE STUDENTS AND GRADUATES TEACHING BIPA - Thomas Wahyu Prabowo Mukti (IJIET (International Journal of Indonesian Education and Teaching), 2020)
Teachers’ identity formation and tension in their working place have been the concern of many researchers and experts. However, the concern focuses only on the novice teachers who teach in the same subject as they are assigned to be. There is no sufficient research on identity tension which is faced specifically. This paper aims to find out the identity tension experienced by English language graduates teaching BIPA (Indonesian as a Foreign Language). This study employed a case study in order to generate a new understanding of this phenomena more deeply. Interview guideline with a semi-structured type of interview became the main instrument in this study. The participants of this study were five active Indonesian as foreign language teachers of Lembaga Bahasa Universitas Sanata Dharma. The study found out that teachers’ situatedness* became the main issue that influences teachers’ identity, compared to teachers’ multifaceted nature and their college. This study shows that, although the participants have been teaching for more than two years, or more, they mostly considered themselves still as English teachers.